1988
DOI: 10.1038/331190a0
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila small cytoplasmic 19S ribonucleoprotein is homologous to the rat multicatalytic proteinase

Abstract: All eukaryotic cells so far analysed contain 19S particles which share a cylinder-like shape and are composed of a set of proteins of relative molecular mass ranging typically from 19,000 to 36,000 (refs 1-10). Proposed functions have included synthetase activity, transfer RNA processing or messenger RNA repression, but their biological importance remains obscure. A multicatalytic proteinase (MCP) of similar size and shape has been isolated from mammalian tissues. The apparent similarities of these high molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(85 citation statements)
references
References 25 publications
4
81
0
Order By: Relevance
“…Falkenburg et al reported that the rat liver multicatalytic proteinase contains RNA molecules in the size range of 80-100 nucleotides [6]. If the multicatalytic proteinase has RNase activity like prosomes, small RNAs present in the proteinase preparation may be hydrolytic products of the enzyme itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Falkenburg et al reported that the rat liver multicatalytic proteinase contains RNA molecules in the size range of 80-100 nucleotides [6]. If the multicatalytic proteinase has RNase activity like prosomes, small RNAs present in the proteinase preparation may be hydrolytic products of the enzyme itself.…”
Section: Discussionmentioning
confidence: 99%
“…Not only did the purified prosome hydrolyze synthetic peptide substrates and [14C]methylcasein, but antibodies raised against 19S prosome specifically reacted with the multicatalytic proteinase and inhibited its protease activity [6,7]. The prosome is known to be a ubiquitous ribonucleoprotein and was identified as mRNA-protein complexes, including globin and other repressed mRNAs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Proteasomes are multicatalytie complexes consisting of a set of non-identical polypeptides, present in both nuclei and cytoplasm of a variety of eukaryoti¢ c~lls from yeast to man [1][2][3] and also described in archaebaeteria [4], In eukaryot~ these particle~ of a sedimentation eoeffmient of about 20 S have a molecular mass around 700 kDa and constitute about 15=20 different subunits ranging from 21 to 32 kDa [5.-6]. but with different p[ values.…”
Section: Introductionmentioning
confidence: 99%
“…They are composed of multiple subunits (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) which are different in size and charge and which are organised into cylindrical 20 S particles [3][4][5][6]. The proteasome catalyses the cleavage of peptide bonds on the carboxyl side of basic, neutral and acidic residues [7][8][9] but its exact function in the cell is still unknown.…”
Section: Introductionmentioning
confidence: 99%